Model studies of advanced glycation end product modification of heterograft biomaterials: The effects of in vitro glucose, glyoxal, and serum albumin on collagen structure and mechanical properties. (15th March 2021) - Rock, Christopher A.; Keeney, Samuel; Zakharchenko, Andrey; Takano, Hajime; Spiegel, David A.; Krieger, Abba M.; Ferrari, Giovanni; Levy, Robert J.
Abstract: Glutaraldehyde cross-linked heterograft tissues, bovine pericardium (BP) or porcine aortic valves, are the leaflet materials in bioprosthetic heart valves (BHV) used in cardiac surgery for heart valve disease. BHV fail due to structural valve degeneration (SVD), often with calcification. Advanced glycation end products (AGE) are post-translational, non-enzymatic reaction products from sugars reducing proteins. AGE are present in SVD-BHV clinical explants and are not detectable in un-implanted BHV. Prior studies modeled BP-AGE formation in vitro with glyoxal, a glucose breakdown product, and serum albumin. However, glucose is the most abundant AGE precursor. Thus, the present studies investigated the hypothesis that BHV susceptibility to glucose related AGE, together with serum proteins, results in deterioration of collagen structure and mechanical properties. In vitro experiments studied AGE formation in BP and porcine collagen sponges (CS) comparing  14 C-glucose and  14 C-glyoxal with and without bovine serum albumin (BSA). Glucose incorporation occurred at a significantly lower level than glyoxal ( p <0.02). BSA co-incubations demonstrated reduced glyoxal and glucose uptake by both BP and CS. BSA incubation caused a significant increase in BP mass, enhanced by glyoxal co-incubation. Two-photon microscopy of BP showed BSA induced disruption of collagen structure that was more severe with glucose or glyoxal co-incubation. Uniaxial testing of CS demonstrated that glucose or glyoxal together with BSA compared to controls, caused accelerated deterioration of viscoelastic relaxation, and increased stiffness over a 28-day time course. In conclusion, glucose, glyoxal and BSA uniquely contribute to AGE-mediated disruption of heterograft collagen structure and deterioration of mechanical properties. Graphical abstract: Image, graphical abstract